2022
DOI: 10.1186/s12891-022-06008-y
|View full text |Cite
|
Sign up to set email alerts
|

AO distractor and manual traction reduction techniques repair in distal tibial fractures: a comparative study

Abstract: Background Minimally invasive plate osteosynthesis (MIPO) via percutaneous plate placement on the distal medial tibia can be performed with minimizes soft tissue injury and produces good clinical results. However, the difficulty with MIPO lies in how to achieve satisfactory fracture reduction and maintain that reduction via indirect reduction techniques to facilitate internal fixation. The purpose of this study was to compare the effects of AO distractor and manual traction reduction techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…These are in line with the ndings of RolandoM et al and further demonstrate that the triangular anchor resurfacing clamp has a superior resurfacing effect. Whereas a previous report [11] compared the e cacy of retractor and manipulative traction repositioning techniques combined with minimally invasive plate osteotomy (MIPO) for distal tibial fractures, they suggested that the di culty in MIPO treatment is to achieve satisfactory fracture repositioning and to maintain this repositioning by indirect repositioning techniques. Interestingly, the same di culty was found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…These are in line with the ndings of RolandoM et al and further demonstrate that the triangular anchor resurfacing clamp has a superior resurfacing effect. Whereas a previous report [11] compared the e cacy of retractor and manipulative traction repositioning techniques combined with minimally invasive plate osteotomy (MIPO) for distal tibial fractures, they suggested that the di culty in MIPO treatment is to achieve satisfactory fracture repositioning and to maintain this repositioning by indirect repositioning techniques. Interestingly, the same di culty was found in our study.…”
Section: Discussionmentioning
confidence: 99%